2016
DOI: 10.1002/marc.201600498
|View full text |Cite
|
Sign up to set email alerts
|

Branched 1,2,3-Triazolium-Functionalized Polyacetylene with Enhanced Conductivity

Abstract: Metathesis cyclopolymerization of mono- or bissubstituted 1,6-heptadiynes is undergone to generate the ionic polyacetylenes (iPAs) with branched 1,2,3-ttriazolium pendants, which possess relatively high intrinsic ionic conductivities of 1.4 × 10 -2.1 × 10 S cm at 30 °C. The doping treatment with lithium bis(trifluoromethanesulfonyl)imide endows iPAs with enhanced ionic conductivities of 2.5 × 10 -4.3 × 10 S cm . Further doping with iodine, iPAs show ionic and electronic dual conductivities of 4.5 × 10 -7.1 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The intrinsic σ i of P ( 1 ‐ co ‐ 3 ) was similar with that of P2 , and thus no further study was given in the following section. The σ i of these iPAs was three orders of magnitude higher than that of neutral PAs with dendronized 1,2,3‐triazole (5.3 × 10 −8 S cm −1 ), higher than those of hyperbranched poly(1,2,3‐triazolium) (7.7 × 10 −6 S cm −1 ) and iPAs with disubstituents of branched 1,2,3‐triazolium (1.9 × 10 −5 S cm −1 ), and even better than that of 1,2,3‐triazolium‐based poly(ionic liquid)s (1.6 × 10 −5 S cm −1 ), likely due to the contribution of high ion density and low T g from the dendronized 1,2,3‐triazolium structure and the flexible OEG groups; of course, poly(siloxane ionic liquid) with 1,2,3‐triazolium‐OEG pendants displayed a slightly higher σ i of 7 × 10 −5 S cm −1 , because of its highly flexible polysiloxane backbone with very low T g of −62 °C.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The intrinsic σ i of P ( 1 ‐ co ‐ 3 ) was similar with that of P2 , and thus no further study was given in the following section. The σ i of these iPAs was three orders of magnitude higher than that of neutral PAs with dendronized 1,2,3‐triazole (5.3 × 10 −8 S cm −1 ), higher than those of hyperbranched poly(1,2,3‐triazolium) (7.7 × 10 −6 S cm −1 ) and iPAs with disubstituents of branched 1,2,3‐triazolium (1.9 × 10 −5 S cm −1 ), and even better than that of 1,2,3‐triazolium‐based poly(ionic liquid)s (1.6 × 10 −5 S cm −1 ), likely due to the contribution of high ion density and low T g from the dendronized 1,2,3‐triazolium structure and the flexible OEG groups; of course, poly(siloxane ionic liquid) with 1,2,3‐triazolium‐OEG pendants displayed a slightly higher σ i of 7 × 10 −5 S cm −1 , because of its highly flexible polysiloxane backbone with very low T g of −62 °C.…”
Section: Resultsmentioning
confidence: 88%
“…Chemical doping is an effective approach to enhance the σ e of PAs. Shirakawa and co‐workers found that the PA film showed a dramatic increase in σ e when doped with controlled amounts of halogens, and particularly, I 2 contributes significantly to increase the σ e of PA. Our group reported that the σ e of I 2 ‐doped PAs reached up to 4.5 × 10 −6 S cm −1 by immersing the as‐prepared polymer film into the saturated I 2 solution of CCl 4 . This method may just change the electrical conducting properties of the polymers on the surface, and the bulk characteristics of polymer doped with I 2 was not revealed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pendant functional groups of polyacetylenes may serve as a tool for introducing or tuning the properties of these polymers, e.g., the conductivity, photoconductivity, specific interaction with molecules or ions, luminescence, helical conformation, and side‐chain liquid crystalline character . Reactive pendant functional groups of polyacetylenes can be moreover chemically modified using various postpolymerization reactions under formation of linear or cross‐linked polymers of modified qualities.…”
Section: Introductionmentioning
confidence: 99%